A microfluidic flow‐focusing device for low sample consumption serial synchrotron crystallography experiments in liquid flow. (13th February 2019) - Monteiro, Diana C. F.; Vakili, Mohammad; Harich, Jessica; Sztucki, Michael; Meier, Susanne M.; Horrell, Sam; Josts, Inokentijs; Trebbin, Martin
Abstract : Serial synchrotron data were collected in flow in a simple microfluidic device under flow‐focusing conditions which allowed sample consumption to be reduced compared with other previously reported liquid‐flow devices. A pulsed data collection strategy prevented the formation of hydrogen bubbles in the chip and the high repetition rate allowed for a short data collection time. Abstract : Serial synchrotron crystallography allows low X‐ray dose, room‐temperature crystal structures of proteins to be determined from a population of microcrystals. Protein production and crystallization is a non‐trivial procedure and it is essential to have X‐ray‐compatible sample environments that keep sample consumption low and the crystals in their native environment. This article presents a fast and optimized manufacturing route to metal–polyimide microfluidic flow‐focusing devices which allow for the collection of X‐ray diffraction data in flow. The flow‐focusing conditions allow for sample consumption to be significantly decreased, while also opening up the possibility of more complex experiments such as rapid mixing for time‐resolved serial crystallography. This high‐repetition‐rate experiment allows for full datasets to be obtained quickly (∼1 h) from crystal slurries in liquid flow. The X‐ray compatible microfluidic chips are easily manufacturable, reliable and durable and require sample‐flow rates on the order of only 30 µl h −1 .